1989
DOI: 10.1148/radiology.170.3.2916037
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate use of bone densitometry.

Abstract: The authors discuss current capabilities of three common bone densitometry techniques--single photon absorptiometry, dual photon absorptiometry, and quantitative computed tomography--and potential capabilities of new innovations of each of these techniques. They believe that use of bone densitometry is valid in the following four clinical applications and recommend its usage to (a) assess patients with metabolic diseases known to affect the skeleton, (b) assess perimenopausal women for initiation of estrogen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
7

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(45 citation statements)
references
References 0 publications
1
36
1
7
Order By: Relevance
“…However, the correlation between calcaneal bone mineral density as measured by DXA and L3 bone mineral density determined by dualenergy quantitative CT was moderate, and the decrement rates for women were different between these bones, suggesting that some limitations may exist when calcaneal bone mineral density is used to assess osteopenia. DXA has several advantages over dual-energy quantitative CT because it offers a lower absorbed dose and better precision than dual-energy quantitative CT does [4]. However, in the spine and femoral neck, which are the preferential sites for bone mineral assessment, DXA measures both the trabecular and cortical portions of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between calcaneal bone mineral density as measured by DXA and L3 bone mineral density determined by dualenergy quantitative CT was moderate, and the decrement rates for women were different between these bones, suggesting that some limitations may exist when calcaneal bone mineral density is used to assess osteopenia. DXA has several advantages over dual-energy quantitative CT because it offers a lower absorbed dose and better precision than dual-energy quantitative CT does [4]. However, in the spine and femoral neck, which are the preferential sites for bone mineral assessment, DXA measures both the trabecular and cortical portions of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Riggs et al [3], demonstrated that the restoration of bone mass with fluoride did not necessarily result in a reduction of fracture rate. On the other hand, in osteoporotic patients a 20%-50% decrease in incidence of new vertebral crush fractures after 2 years treatment has been evidenced by several open prospective studies using the same doses of NaF (50 mg/d) as in our study [9,[14][15][16][17][18]. Thus the crucial question of the anti-fracture effect of NaF remains debatable.…”
Section: Discussionmentioning
confidence: 54%
“…The long-term coefficient of variation (18 months) assessed in young subjects was 2 2 2.2% (0.024 g/cm ) for L2-L4, 1.5% (0.014 g/cm ) for femoral neck and 2.8% (0.021 g/cm 2) for the trochanter [8]. Therefore a variation in vertebral bone density of more than ___ 0.043 g/cm 2 (90% one-tailed confidence limit) between two examinations was considered significant [9].…”
Section: Methodsmentioning
confidence: 98%
“…In recent years, many techniques have been developed for examining bone disease including the measurement of intact parathyroid hormone molecule by radioimmunoassay [21], serum bone alkaline phosphatase, quantitative computed tomography scan and bone density and mineral content by single or dual photon densitometry [22, 23]. Significant correlation of bone histology with i-PTH has been well reported.…”
Section: Discussionmentioning
confidence: 99%